Using Curved Fluid Boundaries to Confine Active Nematic Flows - Khaladj, Dimitrius A.; Hirst, Linda S. (Frontiers in Physics, 2022)
Actively driven, bundled microtubule networks, powered by molecular motors have become a useful framework in which to study the dynamics of energy-driven defects, but achieving control of defect motions is still a challenging problem. In this paper, we present a method to confine active nematic fluid using wetting to curve a layer of oil over circular pillars. This geometry, in which submersed pillars impinge on an oil-water interface, creates a two-tier continuous active layer in which the material is confined above, and surrounds the pillars. Active flows above the pillars are influenced by the circular geometry and exhibit dynamics similar to those observed for active material confined by hard boundaries, e.g., inside circular wells. The thin oil layer beneath the active material is even thinner in the region above the pillars than outside their boundary, consequently producing an area of higher effective friction. Within the pillar region, active length scales and velocities are decreased, while defect densities increase relative to outside the pillar boundary. This new way to confine active flows opens further opportunities to control and organize topological defects and study their behavior in active systems.